Pemikiran Suksesi Dalam Politik Islam Masa Pra Modern - Mazro'atus Sa'adah (AL-TAHRIR, 2016)
Abstract: Islamic political thought emerged after Islam, through Prophet Muhammad, succeeded in forming a new community to transfer the royal power  to the Prophethood power and then to the people power. The Prophet Muhammad was considered successful in arranging his new community that was controlled by his teachings in all aspects of life. The problems arose after his death, which ultimately led to the idea of succession. This article tried to discuss why the succession arose after Prophet Muhammad died, how the thinking of the Islamic political figures of the pre-modern about the succession was, and what the  contribution of this succession to political Islam in Indonesia was. By using a historical approach, it was found that the Prophet Muhammad never specified who would replace him: however, when he died (632 AD), the Sahabats chose a leader (imam/chaliphate). In the reign of era of Abu Bakr, Umar and Usman, many disputes were initially linked to the religion’s interests but later they evolved into a political interests. When Ali bin Abi Talib was appointed as caliph, the prolonged political conflicts linked to the killing of Usman had made caliphate into Jamal war between Aishah and Ali. At this time the different interests of aqidah were politicized further into a political interest. This dynamics of political situation caused the birth of classical Islamic political schools which were divided into three major schools such as Sunni, Shiite and Khawarij, from which emerged the terms caliphate, imamate, ahlul halli wal aqdi, bay'ah, Walayah and others. Of the three political sects, then the idea of Islamic political thought which was very complex  came from  Islamic political leaders of pre-modern heavily influenced by Greek philosophers. In Indonesia, the succession (khilafah) of Islamic political thought at pre-modern times was once under consideration. However, that idea has not been realized because Indonesia is not an Islamic State.الملخص: نشأت الفكرة السياسية الإسلامية منذ نجاح النبي صلى الله عليه وسلّم في تغيير أمة من الرئاسة القبيلية إلى أمة جديدة. هو ناجح في سياسة الأمة على أساس التعاليم الدينية. ظهرت المشكلة بعد وفاة النبيّ صلى الله عليه وسلّم، فبها نشأت الفكرة عن الخلافة. حاولت هذه المقالة إجابة الأسئلة : لما وقعت الخلافة بعد وفاة النبي صلى الله عليه وسلّم ؟، ما أفكار مفكّري السياسة الإسلامية في العصر قبل العصر الحديث عن الخلافة ومدى آثار هذه الأفكار في السياسة الإسلامية في إندونيسيا؟. حصل الباحث – بالمدخل التاريخي – على النتائج، منها أن النبيّ صلى الله عليه وسلّم لا يعيّن من يكون خليفة بعد وفاته. وحين توفّي النبيّ صلى الله عليه وسلّم اختار الصحابة الخليفة. وفي خلافة أبى بكر الصدّيق وعمر وعثمان رضي الله عنهم وقعت خلافات عقائدية ثم تغيّرت إلى نزاعات سياسية. وفي خلافة عليّ بن أبي طالب حدثت خلافات سياسية طويلة عن مقتل عثمان فتؤدّى إلى وقوع معركة الجمل بين عائشة وعليّ بن أبي طالب.  في هذا الحين ظهرت المذاهب السياسية الإسلامية القديمة (أهل السنة والجماعة، والشيعة، والخوارج) ومنها نشأت مصطلحات : الخلافة، والإمامة، وأهل الحلّ والعقد، والبيعة، والولاية وغيرها). ومن هذه المذاهب ظهرت الفكرة السياسية الإسلامية المعقّدة من رجال السياسة الإسلامية قبل العصر الحديث المتأثرة بأفكار فلاسفة اليونان. وقد نوقشت في إندونيسيا الفكرة عن الخلافة  في منظور السياسة الإسلامية في العصر قبل العصر الحديث. ولكن لم تطبّق هذه الأفكار في مجال اختيار رئيس الدولة، لأن إندونيسيا ليست من الدول الإسلامية. Abstrak: Pemikiran politik Islam muncul setelah Islam melalui Nabi Muhammad SAW berhasil membentuk sebuah ummat baru, dari peralihan kekuasaan kerajaan/kesukuan kepada Nabi yang kemudian kepada umat. Nabi Muhammad dinilai berhasil dalam mengatur komunitas barunya yang dikendalikan oleh ajarannya dalam seluruh lini kehidupan. Persoalan muncul kemudian setelah beliau wafat, yang akhirnya memunculkan pemikiran tentang suksesi. Artikel ini akan membahas tentang mengapa terjadi suksesi setelah Nabi Muhammad SAW wafat, bagaimana pemikiran para tokoh politik Islam masa pra modern terkait dengan suksesi, dan apa kontribusi pemikiran suksesi ini terhadap politik Islam di Indonesia. Dengan menggunakan pendekatan sejarah, ditemukan bahwa Nabi Muhammad tidak menetapkan siapa yang akan menggantikannya, dan ketika beliau wafat (632 M), para sahabat memilih seorang pemimpin (imam/khalifah). Masa pemerintahan Abu Bakar, Umar dan Usman banyak terjadi perselisihan yang awalnya terkait kepentingan agama namun berkembang menjadi kepentingan politik. Ketika Ali bin Abi Talib diangkat sebagai khalifah, konflik politik berkepanjangan berkaitan dengan pembunuhan Usman, menjadikan timbulnya perang jamal antara Aisyah dan Ali. Pada masa ini perbedaan kepentingan aqidah dipolitisir lebih jauh menjadi sebuah kepentingan politik. Dinamika politik ini kemudian melahirkan mazhab politik Islam klasik yang terbagi dalam tiga mazhab besar yaitu Sunni, Syi'ah dan Khawarij, yang darinya muncul istilah-istilah khilafah, imamah, ahlul halli wal aqdi, bay’ah, walayah dan lain-lain. Dari ketiga mazhab politik ini, kemudian muncul ide pemikiran politik Islam yang sangat kompleks dan berkepanjangan dari para tokoh politik Islam pra modern yang banyak dipengaruhi oleh filosof Yunani. Di Indonesia, pemikiran suksesi dalam politik Islam masa pra modern ini pernah diwacanakan. Namun untuk pemilihan kepala Negara belum terealisasi mengingat Indonesia bukan Negara Islam.